‘Propolis’ Protective Effect to Prevent Oxidative Stress Caused by Strenous Physical Activity (Swimming Stress) - Hairrudin Hairrudin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Strenous physical activity may give not only a possitive impact but also the negative one. One of the factors that produce negative impact is the increasing formation of oxydant that may cause tissues’ damages. In this kind of circumstances, the oxydant could make damages to the various components in the body, it calls oxydative stress. The effect of the oxydant to the unsaturated fatty acid cause a chain reaction that will break the fatty acid to become different kinds of substances, such as malondialdehid (MDA). The MDA produced then released into the circulatory system, made the serum level of MDA increasing. The influence of propolis as antioxidant may be prevent this problem. This study is a laboratory experiment using posttest-only control group design. The samples of the experiment are 3-month male white rat with average weight between 180-220 grams. These samples are divided to three groups: (1) control group (2) exposure group that have to do strenous activity (30 days swimming stress) and (3) exposure group that have to do strenous activity (30 days swimming stress) and given propolis, each group consists of eight rats. The result of the study showed a higher average serum MDA level in exposure group (89.63 nmol/mL) than the control group (42.38 nmol/ml) significantly (p = 0.000). The influence of propolis could prevent oxidative stress wich was indicated by lower average serum MDA level (32.35 nmol/ml) significanly (p = 0.000).